Resistance of dialyzed patients to erythropoietin - Alves,Michelle Teodoro (2015)
Resistance to recombinant human erythropoietin is a common condition in dialyzed patients with chronic kidney disease and is associated with more hospitalizations, increased mortality and frequent blood transfusions. The main cause of hyporesponsiveness to recombinant human erythropoietin in these patients is iron deﬁciency. However, a high proportion of patients does not respond to treatment, even to the use of intravenous iron, which indicates the presence of other important causes of resistance. In addition to the iron deﬁciency, the most common causes of resistance include inﬂammation, infection, malnutrition, inadequate dialysis, and hyperparathyroidism, although other factors may be associated. In the presence of adequate iron stores, other causes should be investigated and treated appropriately.